Survey on treatments for primary headaches in 13 specialized juvenile Headache Centers: The first multicenter Italian study. (May 2017) - Toldo, Irene; Rattin, Martina; Perissinotto, Egle; De Carlo, Debora; Bolzonella, Barbara; Nosadini, Margherita; Rossi, Livia Nicoletta; Vecchio, Angelo; Simonati, Alessandro; Carotenuto, Marco; Scalas, Cinzia; Sciruicchio, Vittorio; et al.
Abstract: Aim: The purpose of this retrospective multicenter study was to evaluate the use and the self-perceived efficacy and tolerability of pharmacological and non-pharmacological treatments in children and adolescents with primary headaches. Methods: Study of a cohort of children and adolescents diagnosed with primary headache, consecutively referred to 13 juvenile Italian Headache Centers. An ad hoc questionnaire was used for clinical data collection. Results: Among 706 patients with primary headaches included in the study, 637 cases with a single type of headache (migraine 76% – with and without aura in 10% and 67% respectively; tension-type headache 24%) were selected (mean age at clinical interview: 12 years). Acetaminophen and non-steroidal anti-inflammatory drugs (in particular ibuprofen) were commonly used to treat attacks, by 76% and 46% of cases respectively. Triptans were used overall by 6% of migraineurs and by 13% of adolescents with migraine, with better efficacy than acetaminophen and non-steroidal anti-inflammatory drugs. Preventive drugs were used by 19% of migraineurs and by 3% of subjects with tension-type headache. In migraineurs, flunarizine was the most frequently used drug (18%), followed by antiepileptic drugs (7%) and pizotifen (6%), while cyproheptadine, propanolol and amitriptyline were rarely used. Pizotifen showed the best perceived efficacy and tolerability. Melatonin and nutraceuticals were used by 10% and 32% of subjects, respectively, both for migraine and tension-type headache, with good results in terms of perceived efficacy and tolerability. Non-pharmacological preventive treatments (i.e. relaxation techniques, biofeedback, cognitive-behavioral therapy, acupuncture) were used only by 10% of cases (migraine 9%, tension-type headache 15%). Discussion: Non-steroidal anti-inflammatory drugs, especially ibuprofen, should be preferred to acetaminophen for acute attacks of migraine or tension-type headache, because they were usually more effective and well tolerated. Triptans could be used more frequently as first or almost second choice for treating migraine attack in adolescents. Non-pharmacological preventive treatments are recommended by some pediatric guidelines as first-line interventions for primary headaches and their use should be implemented in clinical practice. Prospective multicenter studies based on larger series are warranted to better understand the best treatment strategies for young people with primary headaches. Highlights: Acetaminophen was used more frequently and was less effective than ibuprofen for acute attacks of migraine or TTH. In migraineurs, efficacy of triptans was higher than acetaminophen and ibuprofen. Nutraceuticals were frequently used for migraine and TTH prophylaxis. Other non-pharmacological preventive treatments were rarely used. Available guidelines for primary pediatric headaches should be implemented.